Enhancing Vocabulary Mastery through Brain-Based Learning Strategies: A Study on Junior High School Students - Irmayanti Kusuma; St Asriati AM; Ratna Dewi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Vocabulary plays a critical role in language development, enabling individuals to communicate ideas, comprehend meaning, and foster social interaction. Brain-based learning—an instructional approach aligned with how the brain naturally processes information—engages multiple cognitive functions, such as memory and sensory input, making vocabulary acquisition more effective and durable. This study aimed to examine the effectiveness of brain-based learning in improving students’ vocabulary achievement at SMP Dunia Harapan Makassar. A quantitative research method was employed using a quasi-experimental design. Two groups of eighth-grade students (ages 13–14), each consisting of 20 students, were selected based on similar English proficiency levels determined by a pre-test. The experimental group received instruction using brain-based strategies, while the control group followed traditional methods. Data were collected through vocabulary pre-tests and post-tests. The results revealed a statistically significant improvement in vocabulary scores in the experimental group. The mean post-test score of the experimental group was 90.6, compared to 82.6 in the control group. A t-test analysis confirmed that the difference was statistically significant (p 0.05), indicating that brain-based learning had a positive impact on students’ vocabulary achievement. The findings support the effectiveness of brain-based learning in enhancing vocabulary acquisition among junior high school students. This approach can serve as a valuable strategy for English language instruction. Brain-based learning significantly improves vocabulary achievement. Future studies should explore its long-term effects and broader application in language learning contexts.